Examining how exchange rate fluctuation effects trade balances: emprirically establishing the correlation between exchange rate and balance of trade, the marshall-lerner condition and J effect - Ali, Ratib M; Kamal, Mahsima A (BRAC University, 2012)
Cataloged from PDF version of report.